2019
DOI: 10.2217/bmm-2019-0214
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Research Assessment By Flow Cytometry of Biomarkers for Infectious Stratification in An Emergency Department

Abstract: Aim: Management of patients with infections within the Emergency Department (ED) is challenging for practitioners, as the identification of infectious causes remains difficult with current techniques. A new combination of two biomarkers was tested with a new rapid flow cytometry technique. Materials & methods: Subjects from the ED were tested for their CD64 on neutrophils (nCD64) and CD169 on monocytes (mCD169) levels and results were compared to their clinical records. Results: Among 139 patients, 29% had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Alternatively, overexpression of mCD169 (siglec‐1, one of ISG) by whole blood flow cytometry has been recently proposed as a sensitive and specific surrogate marker of viral infection within the context of early COVID‐19 6 . This marker was previously described as a tool, in conjunction with nCD64 expression, to discriminate bacterial from viral infections at emergency room 5,15 . Specific kinetics of mCD169 expression in response to IFN‐I has been described in vitro 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, overexpression of mCD169 (siglec‐1, one of ISG) by whole blood flow cytometry has been recently proposed as a sensitive and specific surrogate marker of viral infection within the context of early COVID‐19 6 . This marker was previously described as a tool, in conjunction with nCD64 expression, to discriminate bacterial from viral infections at emergency room 5,15 . Specific kinetics of mCD169 expression in response to IFN‐I has been described in vitro 4 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increased mCD169 has been proposed, by itself, as a potential host marker of viral infections (e.g., HIV, influenza). Moreover, in conjunction with concomitant assessment of neutrophil CD64 (nCD64) expression, mCD169 was used to differentiate viral from bacterial infections 5 . Recently, along with increased plasma IFN‐I concentration, mCD169 overexpression was observed in COVID‐19 patients 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the combinatorial detection of CD64 and CD169, respectively, on the surface of neutrophils and monocytes, could be a specific measure for the distinction between the different causes of infections 13 . The main goal of the study was to understand the link that exists between both biomarkers and IFNs produced in response to infections.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Thus, the combinatorial detection of CD64 and CD169, respectively, on the surface of neutrophils and monocytes, could be a specific measure for the distinction between the different causes of infections. 13 The main goal of the study was to understand the link that exists between both biomarkers and IFNs produced in response to infections. The main hypothesis was that the understanding of this functional link could help demonstrate the relevance of using these biomarkers for discriminating between bacterial and viral infections.…”
mentioning
confidence: 99%
“…Indeed, leukocytes detect and rapidly respond to infection with secreted and surface activation molecules. We and others have previously reported that acute viral infections induce the appearance of CD169 (Siglec-1, sialoadhesin) at the surface of blood monocytes (6,7). Monocyte CD169 expression is upregulated by type 1 interferons (8), produced by locally attacked tissues, and is found in all circulating blood monocytes, allowing its detection in minimal blood volumes such as a drop of blood at the fingertip.…”
Section: Introductionmentioning
confidence: 99%